The Tree of Life Web Project* - Maddison, David R.; Schulz, Katja-Sabine; Maddison, Wayne P. (Zootaxa, 2007)
The Tree of Life Web Project (ToL) provides information on the Internet about our current knowledge of the evolutionary tree of life and associated information about characteristics and diversity of life on Earth. Development of this open-access, database-driven system began in 1994; its official release was in 1996. Core scientific content in the project is compiled collaboratively by more than 540 biologists, all experts in particular groups of organisms, from over 35 countries. Additional learning materials are contributed by over 200 students, teachers, and amateur scientists, while images, movies, and sounds are contributed by both of these groups and over 200 media-only contributors. Administration of the project follows a hierarchical, community-based model, with authors for different parts of the ToL chosen by the scientists working in that particular field. The goals of the project are to document all species on Earth, as well as all significant clades; to provide basic information about the phylogeny of life; to share this information with other databases and analytical tools; and to encourage understanding and appreciation for biodiversity, evolution, and the interrelationships of Earth’s wealth of species. Here we provide an outline of the goals and history of the project; the current content, administration, architecture, contributors, and audience, the challenges we have faced, and the future of the project.